Hydrogen-Bonded Conjugated Materials and Their Application in Organic Field-Effect Transistors - Shi, Xin; Bao, Weiwei (Frontiers in Chemistry, 2021)
Recent research in organic semiconductors reveals that not only the composition of the organic material, but also the subtle changes in the material structure (the way how the molecules are stacked) can noticeable effect its bulk properties. One of the reasons is that the charge transport in conjugated materials is strongly affected by their structure. Mobility significantly increases if the conjugated materials exhibit self-assembling properties that can be exploited to generate ordered structures. But well-organized nano-structures are difficult to obtain with classical solution processing methods due to disorder. To obtain well-ordered material films, the simple strategy is synthesis new conjugated materials with ability to self-organize. Introducing a hydrogen-bonding functionality in the materials, resulting in hydrogen-bonded material superstructures, can be a suitable method to fulfil those critical requirements. The formed hydrogen bonds will force to assemble molecules into highly ordered structure, and close the distance between the adjacent molecules, thus enhancing the intermolecular charge-transfer. In this mini-review, small molecules and polymers with hydrogen bonding association, as well as the the relationship between the chemical structures and their performances in organic field effect transistors are reviewed.